Effect of terlipressin on renal function in cirrhotic patients with acute upper gastrointestinal bleeding - Zhang, Jingqiao; Liu, Jie; Wu, Yunhai; Romeiro, Fernando Gomes [UNESP]; Sandri, Giovanni Battista Levi; Zhou, Xinmiao; Li, Miaomiao; Qi, Xingshun (Ame Publ Co, 2020)
Background: Renal dysfunction is a serious morbidity in cirrhotic patients with acute upper gastrointestinal bleeding (AUGIB). Terlipressin is the first-line treatment choice for acute variceal bleeding and hepatorenal syndrome (HRS). This study aimed to assess the effect of terlipressin on renal function in patients with liver cirrhosis and AUGIB. Methods: We retrospectively reviewed 40 cirrhotic patients with AUGIB treated with terlipressin by an attending physician between January 2016 and June 2018. We analyzed the change of renal function parameters, including cystatin C (CysC) and creatinine (Cr), during the use of terlipressin and after terlipressin was stopped. We also identified the factors associated with renal function improvement in patients without active bleeding during the use of terlipressin. Results: During the use of terlipressin, CysC value was significantly reduced (1.3 +/- 0.8 vs. 1.1 +/- 0.7, P=0.001); Cr value was reduced, but the reduction was not statistically significant (68.8 +/- 24 vs. 65.5 +/- 23, P=0.817); the rate of CysC reduction was significantly higher in patients treated with terlipressin than those treated with somatostatin/octreotide (73.1% vs. 0%, P=0.005); the rate of Cr reduction was not significantly different between patients treated with terlipressin and somatostatin/octreotide (61.5% vs. 20%, P=0.148); no factor associated with CysC reduction was identified; higher hemoglobin, red blood cell, and platelet and lower prothrombin time and international normalized ratio at baseline were significantly associated with Cr reduction. After terlipressin was stopped, neither CysC nor Cr value was significantly reduced (P=0.852 and P=0.296). Conclusions: Terlipressin may be beneficial on preventing renal function impairment in cirrhotic patients with AUGIB.
Keywords: Terlipressin; cirrhosis; bleeding; acute kidney injury (AKI); cystatin C (CysC)